Galvanic Restructuring of Exsolved Nanoparticles for Plasmonic and Electrocatalytic Energy Conversion. Issue 29 (13th June 2022) - Kang, Xiaolan; Reinertsen, Vilde Mari; Both, Kevin Gregor; Galeckas, Augustinas; Aarholt, Thomas; Prytz, Øystein; Norby, Truls; Neagu, Dragos; Chatzitakis, Athanasios
Abstract: There is a growing need to control and tune nanoparticles (NPs) to increase their stability and effectiveness, especially for photo‐ and electrochemical energy conversion applications. Exsolved particles are well anchored and can be re‐shaped without changing their initial location and structural arrangement. However, this usually involves lengthy treatments and use of toxic gases. Here, the galvanic replacement/deposition method is used, which is simpler, safer, and leads to a wealth of new hybrid nanostructures with a higher degree of tailorability. The produced NiAu bimetallic nanostructures supported on SrTiO3 display exceptional activity in plasmon‐assisted photoelectrochemical (PEC) water oxidation reactions. In situ scanning transmission electron microscopy is used to visualize the structural evolution of the plasmonic bimetallic structures, while theoretical simulations provide mechanistic insight and correlate the surface plasmon resonance effects with structural features and enhanced PEC performance. The versatility of this concept in shifting catalytic modes to the hydrogen evolution reaction is demonstrated by preparing hybrid NiPt bimetallic NPs of low Pt loadings on highly reduced SrTiO3 supports. This powerful methodology enables the design of supported bimetallic nanomaterials with tunable morphology and catalytic functionalities through minimal engineering. Abstract : Exsolved nanoparticles are galvanically hybridized and new bimetallic nanostructures with tunable photo‐electrocatalytic activity are formed. On the one hand, NiAu nanoconfigurations of improved plasmonic activity compared to monometallic analogues are synthesized and on the other, NiPt bimetallic nanoparticles of high activity toward the hydrogen evolution reaction with low noble‐metal loadings are synthesized. The ease of synthesis through minimal engineering can enable scaled‐up applications.